2000
DOI: 10.1207/s15327752jpa7501_7
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Therapeutic Process and Alliance During Psychological Assessment

Abstract: Utilizing a collaborative therapeutic assessment (TA) model proposed by Finn and Tonsager (1997), we examined the interaction between therapeutic alliance and in-session process during the assessment phase of treatment. This study compares the utility of the TA model (n = 38) versus a traditional information gathering model (n = 90) of assessment. The results of this study indicate that the use of a TA model may decrease the number of patients who terminate treatment against medical advice. The Session Evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(78 citation statements)
references
References 32 publications
7
69
0
2
Order By: Relevance
“…The study compared the utility of the TA model versus a traditional information gathering model of assessment. The results indicated that the use of a TA model may decrease the number of patients who terminate treatment against medical advice, and that the psychological assessment process may impact the patient's experience of assessment feedback and aid in the development of a therapeutic alliance [40].…”
Section: Discussionmentioning
confidence: 99%
“…The study compared the utility of the TA model versus a traditional information gathering model of assessment. The results indicated that the use of a TA model may decrease the number of patients who terminate treatment against medical advice, and that the psychological assessment process may impact the patient's experience of assessment feedback and aid in the development of a therapeutic alliance [40].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Allen et al (1996) found that clients found their therapeutic relationship to be more collaborative when the therapist engaged in clarification or interpretation. In a study by Ackerman et al (2000), clients reported the assessment experience more positively when therapists interacted collaboratively with them to develop treatment goals and engaged in exploring assessment results.…”
Section: Provider Attitudes and Behaviors: Client Perceptions Of Provmentioning
confidence: 99%
“…Ackerman, Hilsenroth, Baity, and Blagys (2000) found that when clients at a community clinic took part in a collaborative assessment prior to beginning formal psychotherapy, they were much less likely to ultimately terminate therapy against medical advice than clients who participated in a more traditional, information gathering model of assessment. In addition, the results presented in Ackerman et al's (2000) article, as well as later results from the same study (Hilsenroth, Peters, & Ackerman, 2004), indicated collaborative assessment may be associated with higher levels of client-therapist alliance during subsequent psychotherapy when compared with alliance levels reported by clients who received traditional assessment. Similarly, Hanson, Claiborn, and Kerr (1997) found that college students participating in a brief "interactive" (collaborative) assessment were more likely to rate their sessions "deep" and their counselors as expert, trustworthy, and attractive, than students participating in an assessment that involved unilateral feedback from the assessor.…”
Section: Empirical Research On Collaborative and Therapeutic Assessmementioning
confidence: 99%
“…To date, all of the empirical research on collaborative and Therapeutic Assessment has focused on individual (Ackerman et al, 2000;Finn & Tonsager, 1992;Hilsenroth et al, 2004;Newman & Greenway, 1997) and family clients (Smith et al, 2009;Tharinger et al, 2009;Tharinger, Finn, Wilkinson, & Schaber, 2007). However, an accumulating body of case material suggests collaborative and Therapeutic Assessment techniques may also be useful for psychologists working with couples, either as a precursor or supplement to traditional couples therapy (Butcher, 1990;Dorr, 1981;Finn, 2007;Richman & Davidoff, 1971).…”
Section: Empirical Research On Collaborative and Therapeutic Assessmementioning
confidence: 99%
See 1 more Smart Citation